Reliability and risk modeling of engineering systems - Panchal, Dilbagh 1982-; Chatterjee, Prasenjit; Pamucar, Dragan; Tyagi, Mohit (Springer, 2021)
This book addresses reliability, maintenance, risk, and safety issues of industrial systems with applications of the latest decision-making techniques. Thus, this book presents chapters that apply advanced tools, techniques, and computing models for optimizing the performance of industrial and manufacturing systems, along with other complex engineering equipment. Computing techniques like data analytics, failure mode and effects analysis, fuzzy set theory, petri-net, multi-criteria decision-making (MCDM), and soft computing are used for solving problems of reliability, risk, and safety related issues. Discusses reliability, risk, and safety issues of industrial systems with the application of the latest reliability and risk based modelling; Includes a wide range of applications related to reliability and risk modeling of engineering systems; Presents a collection of a diverse range of case studies and uses methods to let readers apply cutting-edge decision making methods to their own projects.